A csehszlovák-magyar lakosságcsere hatásai a lokális társadalmakra : esettanulmány Véméndről - Szalai, Gábor (Közép-Európai Közlemények, 2009)
I wished to present the trials and integration difficulties in their new homes of Hungarians deported from Czechoslovakia in my study. I wished to describe how the Hungarians of Felvidék lived together with native Germans and resettled Szeklers ones living on the settlement, what helped and what set back their peaceful relationship. The examination showed that the greatest offence of Hungarians of Slovakia (the lack of cemeteries and churches) was originated from the differences of their religions. The different kind of farming which they had to face in Baranya county made the integration harder. On the other hand the fact that the Germans and the Szeklers ones admitted them easily made the Slovakian Hungarians’ life easier. This was due to the mentality and financial status of the Slovakian Hungarians’.